2020
DOI: 10.1371/journal.pone.0229669
|View full text |Cite
|
Sign up to set email alerts
|

Low utilization of glucose in the liver causes diet-induced hypercholesterolemia in exogenously hypercholesterolemic rats

Abstract: Exogenously hypercholesterolemic (ExHC) rats develop diet-induced hypercholesterolemia (DIHC) when fed with dietary cholesterol. Previously, we reported that, under the highsucrose-diet-feeding condition, a loss-of-function mutation in Smek2 results in low activity of fatty acid synthase (FAS) followed by the shortage of hepatic triacylglycerol content in ExHC rats and the onset of DIHC. However, the relationship between the Smek2 mutation and FAS dysfunction is still unclear. Here, we focused on carbohydrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The ExHC rats developed hypersarcosinemia and further homocysteinemia due to abnormal sarcosine metabolism caused by decreased Sardh expression. In addition to regulating glucose metabolism 4 , 5 , Smek2 is also important for regulating amino acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ExHC rats developed hypersarcosinemia and further homocysteinemia due to abnormal sarcosine metabolism caused by decreased Sardh expression. In addition to regulating glucose metabolism 4 , 5 , Smek2 is also important for regulating amino acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This deletion leads to disrupted SMEK2 protein function that is not fatal in rats. With respect to the pathological mechanism of DIHC in ExHC rats, we found that compared with the original Sprague–Dawley (SD) strain, ExHC rats have impaired liver glucose metabolism (low expression of liver-type phosphofructokinase, Pfkl , a rate-limiting enzyme of glycolysis) 4 , low de novo fatty acid synthesis in the liver due to a shortage of required precursors 5 , and that this shortage of fatty acids leads to hepatic secretion of β-VLDL that is slowly uptaken by the liver 5 . However, the mechanism of Pfkl downregulation by the loss-of-function of Smek2 is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such elevated serum cholesterol levels are considered a high-risk pathogenic factor for atherosclerosis (18) . Animal model studies have shown that a high-dietary cholesterol intake increases total serum cholesterol levels in ApoE -/ -mice and ExHC rats (19,20) . Additionally, compositions of dietary fatty acids are also an important factor for serum cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…ExHC rats were established from Sprague-Dawley (SD) rats as a model of diet-induced hypercholesterolemia. 13 Their serum total cholesterol levels increase only when fed a cholesterol-containing diet without dietary bile salt as a result of disorders in carbohydrate metabolism, 14 not of excessive cholesterol synthesis in the liver. Therefore, ExHC rats enables to design more physiological, bile-salt-free dietary condition.…”
Section: Introductionmentioning
confidence: 99%